(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Backgrounds: This study examined salad consumption in relation to daily dietary intake and diet quality among U.S. adults. Methods: Nationally representative sample came from the National Health and Nutrition Examination Survey 2003-2012 waves. Salad consumption was identified through both Food and Nutrient Database for Dietary Studies codes for salad items and combination code for components of and/or additions to salads. First-difference estimator addressed confounding bias from time-invariant unobservables (e.g., eating habits, taste preferences) by using within-individual variations in salad consumption between 2 nonconsecutive 24-hour dietary recalls. Results: Approximately 28.7% of U.S. adults consumed salad on any given day. Among salad consumers, salad consumption occupied 12.5% of daily total energy, 62.8% vegetable, 11.9% fruit, 18.4% fiber, 9.1% sugar, 20.3% total fat, 14.7% saturated fat, 14.9% cholesterol, and 17.7% sodium intake. Compared to no salad consumption on a dietary recall day, salad consumption was associated with increased daily intake of total energy by 461.5 kJ (110.3 kcal), vegetable 85.0 g, fiber 1.0 g, sugar 5.7 g, total fat 10.0 g, saturated fat 1.3 g, cholesterol 18.7 mg, and sodium 216.3 mg. Salad consumption was associated with an increase in the Healthy Eating Index-2010 score by 4.2. Conclusion: Salad consumption is related to better overall diet quality but also higher total energy, sugar, fat, cholesterol, and sodium intake. Interventions that promote salad consumption should provide low-energy-dense, nutrient-rich salad products. Salad consumers should prudently evaluate the caloric and nutrient content of salad in order to make informed and more healthful diet choices.